Impact of left ventricular outflow tract flow acceleration on aortic valve area calculation in patients with aortic stenosis - Ahmed, Andaleeb A (Echo Res Pract, 2019)
OBJECTIVE: Due to its circular shape, the area of the proximal left ventricular tract (PLVOT) adjacent to aortic valve can be derived from a single linear diameter. This is also the location of flow acceleration (FA) during systole, and pulse wave Doppler (PWD) sample volume in the PLVOT can lead to overestimation of velocity (V(1)) and the aortic valve area (AVA). Therefore, it is recommended to derive V(1) from a region of laminar flow in the elliptical shaped distal LVOT (away from the annulus). Besides being inconsistent with the assumptions of continuity equation (CE), spatial difference in the location of flow and area measurement can result in inaccurate AVA calculation. We evaluated the impact of FA in the PLVOT on the accuracy of AVA by continuity equation (CE) in patients with aortic stenosis (AS). METHODS: CE-based AVA calculations were performed in patients with AS once with PWD-derived velocity time integral (VTI) in the distal LVOT (VTI(LVOT)) and then in the PLVOT to obtain a FA velocity profile (FA-VTI(LVOT)) for each patient. A paired sample t-test (P < 0.05) was conducted to compare the impact of FA-VTI(LVOT) and VTI(LVOT) on the calculation of AVA. RESULT: There were 46 patients in the study. There was a 30.3% increase in the peak FA-VTI(LVOT) as compared to the peak VTI(LVOT) and AVA obtained by FA-VTI(LVOT) was 29.1% higher than obtained by VTI(LVOT). CONCLUSION: Accuracy of AVA can be significantly impacted by FA in the PLVOT. LVOT area should be measured with 3D imaging in the distal LVOT.